Dividend Payout Policy and Global Financial Crisis: A Study on Asian Non-Financial Listed Companies - Boo, Hooi-Laing; Chan, Tze-Haw (Asian Economic and Financial Review, 2022)
This study assesses the dividend payout options of non-financial firms listed on the stock exchanges in four Asian countries: Malaysia, Thailand, Singapore and Hong Kong, from 2006–2016. Multinomial logistic regression was used to justify the determinants of four mutually exclusive payout choices (increase, cut, omit or maintain) in the context of catering, signaling and smoothing concerns. The study is split into pre-, during and post-crisis periods. Several dividend patterns were observed across the nations and sub-periods, and the empirical results reveal that firms shifted their dividend policy during the financial crisis. More specifically, firms adopted a conservative strategy and were more concerned about preserving funds rather than distributing dividends during the financial crisis. The consequence is broadly consistent with the view that the dividend payer’s characteristics are the most relevant to explaining the dividend payout options, while cutting dividends was one of the methods used to maintain financial flexibility during the financial crisis period.